let X be non empty set ; :: thesis: for S being SigmaField of X
for f being with_the_same_dom Functional_Sequence of X,REAL
for g being PartFunc of X,ExtREAL
for E being Element of S st dom (f . 0) = E & ( for n being Nat holds f . n is E -measurable ) & dom g = E & ( for x being Element of X st x in E holds
( f # x is convergent & g . x = lim (f # x) ) ) holds
g is E -measurable

let S be SigmaField of X; :: thesis: for f being with_the_same_dom Functional_Sequence of X,REAL
for g being PartFunc of X,ExtREAL
for E being Element of S st dom (f . 0) = E & ( for n being Nat holds f . n is E -measurable ) & dom g = E & ( for x being Element of X st x in E holds
( f # x is convergent & g . x = lim (f # x) ) ) holds
g is E -measurable

let f be with_the_same_dom Functional_Sequence of X,REAL; :: thesis: for g being PartFunc of X,ExtREAL
for E being Element of S st dom (f . 0) = E & ( for n being Nat holds f . n is E -measurable ) & dom g = E & ( for x being Element of X st x in E holds
( f # x is convergent & g . x = lim (f # x) ) ) holds
g is E -measurable

let g be PartFunc of X,ExtREAL; :: thesis: for E being Element of S st dom (f . 0) = E & ( for n being Nat holds f . n is E -measurable ) & dom g = E & ( for x being Element of X st x in E holds
( f # x is convergent & g . x = lim (f # x) ) ) holds
g is E -measurable

let E be Element of S; :: thesis: ( dom (f . 0) = E & ( for n being Nat holds f . n is E -measurable ) & dom g = E & ( for x being Element of X st x in E holds
( f # x is convergent & g . x = lim (f # x) ) ) implies g is E -measurable )

assume that
A1: dom (f . 0) = E and
A2: for n being Nat holds f . n is E -measurable and
A3: dom g = E and
A4: for x being Element of X st x in E holds
( f # x is convergent & g . x = lim (f # x) ) ; :: thesis: g is E -measurable
A5: dom (lim f) = E by ;
now :: thesis: for x being Element of X st x in dom (lim f) holds
g . x = (lim f) . x
let x be Element of X; :: thesis: ( x in dom (lim f) implies g . x = (lim f) . x )
assume A6: x in dom (lim f) ; :: thesis: g . x = (lim f) . x
then x in E by ;
then f # x is convergent by A4;
then lim (f # x) = lim (R_EAL (f # x)) by RINFSUP2:14;
then g . x = lim (R_EAL (f # x)) by A4, A5, A6;
hence g . x = (lim f) . x by ; :: thesis: verum
end;
then A7: g = lim f by ;
for x being Element of X st x in E holds
f # x is convergent by A4;
hence g is E -measurable by A1, A2, A7, Th21; :: thesis: verum